2006
DOI: 10.1074/jbc.m602689200
|View full text |Cite
|
Sign up to set email alerts
|

BM88 Is a Dual Function Molecule Inducing Cell Cycle Exit and Neuronal Differentiation of Neuroblastoma Cells via Cyclin D1 Down-regulation and Retinoblastoma Protein Hypophosphorylation

Abstract: Control of cell cycle progression/exit and differentiation of neuronal precursors is of paramount importance during brain development. BM88 is a neuronal protein associated with terminal neuron-generating divisions in vivoThe formation of the nervous system is governed by a delicate balance between cell proliferation, subsequent cell cycle withdrawal, and differentiation to distinctive neuronal phenotypes (1, 2). Current observations have highlighted the existence of mechanisms coupling cell cycle exit and dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
83
0
11

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(101 citation statements)
references
References 78 publications
(85 reference statements)
7
83
0
11
Order By: Relevance
“…Here, we demonstrated that BM88 is necessary for proper regulation of proliferation and neuronal differentiation of NPCs derived from embryonic mouse spinal cord. In agreement, we have recently reported that BM88 knockdown in a neuroblastoma cell line enhanced proliferation and impaired retinoic acid-induced neuronal differentiation (11). Collectively, these data implicate BM88 in synchronization of cell cycle exit and neuronal lineage progression.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Here, we demonstrated that BM88 is necessary for proper regulation of proliferation and neuronal differentiation of NPCs derived from embryonic mouse spinal cord. In agreement, we have recently reported that BM88 knockdown in a neuroblastoma cell line enhanced proliferation and impaired retinoic acid-induced neuronal differentiation (11). Collectively, these data implicate BM88 in synchronization of cell cycle exit and neuronal lineage progression.…”
Section: Discussionsupporting
confidence: 76%
“…Thus, although its effect on cell cycle exit is similar along the dorsoventral axis of the neural tube, the effect on neuron generation is more successfully terminated in the ventral spinal cord within the MN domain. A similar context-dependent requirement for the neurogenic potential of BM88 was noted in vitro (11). Thus, BM88 induces neurogenesis in neural cells possessing the appropriate machinery for neuronal differentiation, whereas it seems to direct nonneural cells toward cell cycle exit and, eventually, to a proapoptotic pathway.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Our data have shown that loss of Hap1 can lead to enhanced interaction between Dcaf7 and DYRK1A, resulting in an increase in DYRK1A. It has been reported that increased DYRK1A can affect cell-cycle regulation and neuronal differentiation by reducing cyclin D1 and the cyclindependent kinase inhibitor p21 (49,50), two important proteins that promote neuronal differentiation (50)(51)(52)(53)(54). Thus, we isolated hypothalamic tissues from WT and Hap1-KO postnatal pups and performed Western blotting with anti-cyclin D1 and anti-p21.…”
Section: Hap1 Stabilizes the Protein Level Of Dcaf7 By Inhibiting Itsmentioning
confidence: 88%